Nilai-Nilai Pendidikan Akhlak Dalam Kitab Ta’lim Al Muta’alim Dan Relevansinya Dengan Pendidikan Karakter Di Era 5.0 - Sadiyah, Siti Mahbubatus; ., Maskunatin; Junaidi, Mahbub; Taurus Tamaji, Sampiril (Fakultas Agama Islam, 2024)
This research is motivated by the many irregularities in the era of information and communication technology advances. One way that can be done to reduce or even eliminate deviations that occur is by studying moral education and character education. One of the books that can be used as a guide in learning moral education and character education is the Book of Muta’alim ta’lim. This study aims to find out 1. the values of moral education in the Book of Ta’lim Muta’alim, 2. what the values of moral education in the Book of Ta’lim Muta’alim and their relevance to character education in the 5.0 era. This research is a library (library research) with a literature study approach. These research results are eleven moral education values in the Book of Muta’alim ta’lim relevant to character education in the 5.0 era. With the application of moral education in the Book of ta’lim muta’alim, which is relevant to character education in the era of advances in information and communication technology, it is hoped that it will be able to produce generations of good morals, intelligent and qualified who can take advantage of advances in information and communication technology properly and wisely.